Encyclopedia of violence, peace & conflict - Kurtz, Lester R.; Turpin, Jennifer E. (San Diego : Academic Press, 1999)
"This outstanding three-volume set seeks to answer basic questions about modern warfare, conflict, violence, and peace, but also covers current topics such as police brutality, aggression in sports, television violence, and animal aggression. The greatest value of this multivolume work is its interdisciplinary coverage. The set is broken down into 15 subject areas covering approximately 200 different issues. Each article is about 9,000 words, including a definition of the subject, illustrations, glossaries, and bibliographies. It is an excellent source written by scholars from around the world."--"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
v. 1. A - E -- v. 2. F - Pe -- v. 3. Po - Z, Index.
Includes bibliographical references and index.
Keywords: Violence -- Encyclopedias; Conflict (Psychology) -- Encyclopedias; Social conflict -- Encyclopedias; Peace -- Encyclopedias